Uji Efektivitas Beberapa Jenis Tanaman Berpotensi Bioherbisida untuk Mengendalikan Gulma Babadotan (Ageratum conyzoides): Effectivity Test of Several Plants with Bioherbicide Potential to Control Ageratum conyzoides Weeds - Karti Rahayu Kusumaningsih (HUTAN TROPIKA, 2021)
Several plants founded in the field, for examples Swietenia macrophylla, Imperata cilindrica, carica papaya and Morinda citrifolia have chemical compounds that can be used as bioherbicide. The purpose of this research are to know content of Tannin and Flavonoid compounds in that plants and effect of interaction between type of leaf extract and bioherbicide solution formula i.e 10%, 20% and 30% againts effectivity of Ageratum conyzoides weeds control. Results of the research showed that leaf extract of S. macrophylla, I. cilindrica, C. papaya and M. citrifolia contain of Tannin and Flavonoid compounds with bioherbicide potential, with highest contain in S. macrophylla and lowest in I. cilindrica leaf extract. Interaction of type of leaf extract and solution formula gived very significant effect againts percentage of weed mortality and weed poisoning intensity of A. conyzoides weeds. Leaf extract of S. macrophylla, C. papaya and M. citrifoilia with 10-30% solution formula, were effective to control A. conyzoides weeds, with average of start time of weeds death was 3 days after bioherbicide application. Keywords : Bioherbicide, leaf extract, percentage of weed mortality, weed poisoning intensity